1987
DOI: 10.1038/329246a0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage of bilateral acoustic neurofibromatosis to a DNA marker on chromosome 22

Abstract: Bilateral acoustic neurofibromatosis (BANF) is a severe autosomal dominant disorder involving development of multiple tumours of the nervous system including meningiomas, gliomas, neurofibromas and particularly bilateral acoustic neuromas. We have used genetic linkage analysis with DNA markers to establish that the defective gene causing BANF is on chromosome 22, and is therefore distinct from the gene for the von Recklinghausen form of neurofibromatosis, which maps to chromosome 17. Linked DNA markers will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(115 citation statements)
references
References 13 publications
1
112
0
2
Order By: Relevance
“…2,3 Our outcomes were more positive, possibly as a result of these being newly diagnosed cases. This was achieved without fluorescein angiography.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…2,3 Our outcomes were more positive, possibly as a result of these being newly diagnosed cases. This was achieved without fluorescein angiography.…”
mentioning
confidence: 74%
“…2 It is characterized by bilateral vestibular schwannomas, that is, 'acoustic neuromas'. Other central nervous tumours may also occur, such as meningeomas of the brain, schwannomas of other cranial nerves, spinal nerve roots, and peripheral nerves and gliomas.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…In this syndrome there is loss of heterozygosity for markers on chromosome lp, but not for markers on chromosome 10 (Mathew et al, 1987b). (Meese et al, 1987;Seizinger et al, 1986Seizinger et al, , 1987 (Rouleau et al, 1987). One patient who died with multiple meningiomas had a constitutional abnormality of chromosome 22 (Arinami et al, 1986).…”
Section: Wilms' Tumour and Rhabdomyosarcomamentioning
confidence: 99%
“…Male and female patients are approximately equally affected [3]. Until 1987 neurofibromatosis type 1 and 2 were considered one single disease, but it was then demonstrated that the two disorders arose from different mutations in different chromosomes [4]. NF2 is an inheritable disorder with an autosomal dominant mode of transmission, associated with chromosome 22q12 [5].…”
Section: Introductionmentioning
confidence: 99%